Indikator Partisipasi Mahasiswa dalam Perencanaan Studi di Perguruan Tinggi Berdasarkan Perspektif Kesetaraan Gender: Penelitian di STAI Yapata Al-Jawami Bandung - Oktaviani, Nia (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2025)
The concept of gender refers to men and women in their roles, behaviors, activities, and socially constructed attributes. Fairness between the two will eliminate this difference. This study aims to analyze student participation in study planning in higher education based on several indicators: goals, motivation, basis, personal desires, reasons for choosing a study program, and expectations. This study uses a qualitative descriptive research method using a gender equality perspective and a focused group discussion (FGD) technique with thematic analysis to identify data according to the theme. The study results show differences between male and female students in terms of the purpose of continuing their studies, where female students aim more to get a diploma, while male students have more diverse goals, such as increasing knowledge or increasing religious knowledge. The main motivation for students is the demands of work and the desire to be successful, with additional motivation for female students to be good mothers. Most students' main basis for continuing their studies is improving their quality of life and the desire to practice knowledge. Most students are internally motivated to pursue higher education, indicating a strong personal drive without significant external influences. The choice of study program is based on the desire to become a professional, such as becoming a teacher for the PAI Study Program and deepening Islamic economic law for the HESy Study Program. Expectations after completing studies include the desire to become a useful individual in society, with male students tending to want to continue to the Masters level, while female students are more likely to work immediately. Active participation in this planning shows that clear motivation and goals are important indicators of the success of students' studies in higher education. Keywords: gender equity, study planning, higher education